Production Performance and Carcass Quality of Male Bali Cattle by Feeding Fermented Pineapple Peel - Bulkaini Bulkaini (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2022)
Bali cattle are local Indonesian cattle that were first developed on the island of Bali with unique properties, namely resistance to heat grip and not selective for feed. This research was conducted to assess the production performance and carcass quality of male Bali cattle by feeding fermented pineapple peel. The materials and methods used were twelve male Bali cattle with an average initial weight of 168.46 ± 11.95 kg placed in individual cages randomly based on a Completely Randomized Design with 3 treatments and 4 tails as replications. namely: T0=Native grasses +(39% milled corn+61% rice bran+0% fermented pineapple peel); T1=Native grasses +(10% milled corn+70% bran+20% fermented pineapple skin with tape yeast); and T2=Native grasses +(15% milled corn +65% bran+20% pineapple peel fermented by lactic acid bacteria). The research data consisting of production performance and carcass quality were analyzed by analysis of variance using the SPSS version 16 software program and continued with Duncan's test at the 5% confidence level. The results showed that the addition of pineapple peel fermented by lactic acid bacteria as much as 20% in the ration could provide the highest daily body weight gain of male Bali cattle (0.66 kg/head/day), low FCR (8.01), high protein consumption (630.18g/head/day), high carcass percentage (55.17%), high meat index (1.00) with large rib eye area (55.97 cm2). Conclusion: The addition of pineapple peel fermented by lactic acid bacteria in the ration of as much as 20% can improve the production performance and carcass quality of male Bali cattle.